Pharmacology - Jacob, Leonard S. (Malvern, Pennsylvania : Williams & Wilkins ; Harwal, Baltimore, 1992)
Third edition has been extensively revised to reflect the up-to-date treatment of new diseases, such as AIDS and Lyme disease, as well as new treatment of old diseases, such as fungal infections and congestive heart failure.
General pharmacologic principles -- Drugs affecting peripheral neurohumoral transmission -- Agents acting on the central nervous system -- Anesthetic agents -- Cardiovascular agents -- Diuretic agents -- Drugs affecting hematopoiesis and hemostasis -- Autocoids and their antagonists -- Non-narcotic analgesics, nonsteroidal anti-inflammatory drugs, and drugs used in the treatment of gout -- Hormones, antagonists, and other agents affecting endocrine function -- Cancer chemotherapy -- Anti-infective agents -- Principles of drug interactio
Includes index.
Keywords: PHARMACOLOGY -- EXAMINATIONS, QUESTION, ETC